Terrible triad of the elbow: evaluation of surgical treatment - Galbiatti, José Antonio (2018)
ABSTRACTObjective: This study aims at analyzing retrospectively the clinical-functional and radiographic results of surgical treatment of the terrible elbow triad, with at least 12 months of postoperative follow-up evaluating elbow function.Methods: A group of patients for retrospective analysis from 2004 to 2015 was defined, in which 12 patients were studied. They underwent surgery due to fracture of the radial head, coronoid fracture, and elbow dislocation; they were evaluated by the Disabilities of the Arm, Shoulder and Hand (DASH) score, the degree of patient satisfaction, the degree of trauma energy, radiographic images, range of motion, and complications.Results: There was a higher incidence of Regan and Morrey type II coronoid process fractures; in relation to the injuries, nine patients had deinsertion of the brachialis. Half of the patients suffered a fall from their own height as the mechanism of trauma. The extent of elbow flexion and extension averaged 126.6 and 24.1 degrees, respectively; the averages for pronation and supination were 64.1 and 62.0 degrees, respectively. All patients presented muscle strength of grade IV or V. The mean DASH score was 14.3, the mean pain score was 2.5, and a majority of the patients were satisfied with the treatment.Conclusion: Despite the total loss of range of motion of the elbow, especially in extension, the treatment was satisfactory for most patients.